Peptidic boronic acid Plasmodium falciparum SUB1 inhibitors with improved selectivity over human proteasome - Withers-Martinez, Chrislaine (J Med Chem, 2024)
Plasmodium falciparum subtilisin-like serine protease 1 (PfSUB1) is essential for egress of invasive merozoite forms of the parasite, rendering PfSUB1 an attractive antimalarial target. Here we report studies aimed to improve drug-like properties of peptidic boronic acid PfSUB1 inhibitors including increased lipophilicity and selectivity over human proteasome (H20S). Structure-activity relationship investigations revealed that lipophilic P(3) amino acid side chains as well as N-capping groups were well tolerated in retaining PfSUB1 inhibitory potency. At the P(1) position, replacing the methyl group with a carboxyethyl substituent led to boralactone PfSUB1 inhibitors with remarkably improved selectivity over H20S. Combining lipophilic end-capping groups with the boralactone reduced the selectivity over H20S. However, compound 4c still showed >60-fold selectivity versus H20S and low nanomolar PfSUB1 inhibitory potency. Importantly this compound inhibited growth of a genetically modified P. falciparum line expressing reduced levels of PfSUB1 13-fold fold more efficiently compared to a wild-type parasite line.